NiO–CGO in situ nanocomposite attainment: one step synthesis - Cela, Beatriz (2011)
The CeO2-based electrolyte low temperature SOFCs require special electrodes with a higher performance and compatibility. The performance of the CeO2-based composite anodes depends on microstructural features such as particle size, tripe phase boundaries (TPB), surface area, and percolation. Some of the primary parameter can be manipulated during the materials synthesis. In this work the compound NiO–Ce0.9Gd0.1O1.95 (NiO–CGO), used as anode in SOFC, was synthesized by two different processes. Both of them are based on the polymeric precursormethod. Characterized by simultaneous thermogravimetry-differential thermal analysis, X-ray diffraction, scanning electron microscopy, Fourier transform infrared spectroscopy and dilatometry. The refinement of the XRD data indicated that the composite sample synthesized by the process called “one step synthesis” produced smaller crystallite size in comparison to the sample attained by the two steps process. Simple preliminary performance tests were done with single cells in which such I–V curves indicated that the cell with one step anode had better performance. “One step synthesis” product, in situ nanocomposite, presented similar fine grained particle sizes for both phases Ni and CGO, which would be beneficial to the electrochemical activity, also indicated by first performance tests